Determination of Available and Digestible Phosphorus Release of Microtech Phytase in Nursery Pig Diets - Ron Aldwin S. Navales; Katelyn N. Gaffield; Ty H. Kim; Joel M. DeRouchey; Paul Martin; Juan A. Javierre; Jordan T. Gebhardt; Robert D. Goodband; Mike D. Tokach; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 320 barrows (DNA 200 × 400; initially 23.6 ± 0.47 lb) were used in a 21-d growth trial to determine the available P (aP) and true total tract digestible P (TTTD P) release curves for Microtech phytase (Guangdong VTR Bio-Tech Co, Ltd. Zhuhai, Guangdong, China). At approximately 21 d of age, pigs were weaned and randomly allocated to pens and fed a common diet for 18 d and then fed a P depletion diet (0.11% aP and 0.20% STTD P) for 3 d. On d 21 post-weaning, considered d 0 of the study, pigs were blocked by average pen body weight (BW) and randomly allotted to one of eight dietary treatments with five pigs per pen and eight pens per treatment. Dietary treatments were derived from a single basal diet and phytase, monocalcium phosphate, limestone, and sand were added to create the treatment diets. Treatments included three diets with increasing aP (0.11, 0.19 and 0.27%) and STTD P (0.20, 0.27 and 0.35%) using monocalcium phosphate that were used to develop the standard curves for the determination of aP and TTTD P release, and five diets with 0.11% aP (0.20% STTD P) and increasing phytase (250, 500, 1,000, 1,500 and 2,000 FTU/kg) that were used to develop the aP and TTTD P release curves. Pigs were weighed weekly, and feed disappearance was recorded per pen for the calculation of ADG, ADFI and F/G. At d 14 of the trial, fecal samples were collected from three pigs per pen. Samples were oven dried, ground, pooled per pen and analyzed for dry matter (DM), N, P and TiO2 for the calculation of apparent total tract digestibility (ATTD) of DM, N and P. At the conclusion of the experiment, one pig, closest to the mean weight of each pen, was euthanized for bone analysis. The right fibula, right tenth rib, and right third metacarpal were collected for the determination of bone density, bone ash weight, and percentage bone ash. Increasing aP (and STTD P) from inorganic P improved (quadratic, P ≤ 0.05) final BW, ADG, and F/G. Increasing phytase increased (linear, P < 0.02) final BW and ADFI and improved (quadratic, P ≤ 0.05) ADG and F/G. Dry matter digestibility decreased (quadratic, P < 0.05) with increasing aP (and STTD P) from inorganic P, while P digestibility increased (linear, P < 0.01) with increasing aP (and STTD P) from inorganic P and increasing phytase. Bone density, bone ash weight, and percentage bone ash increased (linear, P < 0.01) with increasing aP (STTD P) from inorganic P and increasing phytase. Results from average percentage bone ash of the three bones and P digestibility were used to determine the aP and TTTD P release values, respectively. The aP and STTD P release curves developed for Microtech phytase are: aP release, % = (0.868 × FTU/kg) ÷ (9,599.511 + FTU/kg) and TTTD P release, % = (4.017e-5 × FTU) + 0.011, respectively.
Keywords: available P; digestible P; phytase; nursery pig